Identification of Acinetobacter Species Using Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry - Jeong, Seri; Hong, Jun Sung; Kim, Jung Ok; Kim, Keon-Han; Lee, Woonhyoung; Bae, Il Kwon; Lee, Kyungwon; Jeong, Seok Hoon (Annals of laboratory medicine, 2016)
Acinetobacter baumannii has a greater clinical impact and exhibits higher antimicrobial resistance rates than the non-baumannii Acinetobacter species. Therefore, the correct identification of Acinetobacter species is clinically important. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) has recently become the method of choice for identifying bacterial species. The purpose of this study was to evaluate the ability of MALDI-TOF MS (Bruker Daltonics GmbH, Germany) in combination with an improved database to identify various Acinetobacter species. A total of 729 Acinetobacter clinical isolates were investigated, including 447 A. baumannii, 146 A. nosocomialis, 78 A. pittii, 18 A. ursingii, 9 A. bereziniae, 9 A. soli, 4 A. johnsonii, 4 A. radioresistens, 3 A. gyllenbergii, 3 A. haemolyticus, 2 A. lwoffii, 2 A. junii, 2 A. venetianus, and 2 A. genomospecies 14TU. After 212 isolates were tested with the default Bruker database, the profiles of 63 additional Acinetobacter strains were added to the default database, and 517 isolates from 32 hospitals were assayed for validation. All strains in this study were confirmed by rpoB sequencing. The addition of the 63 Acinetobacter strains' profiles to the default Bruker database increased the overall concordance rate between MALDI-TOF MS and rpoB sequencing from 69.8% (148/212) to 100.0% (517/517). Moreover, after library modification, all previously mismatched 64 Acinetobacter strains were correctly identified. MALDI-TOF MS enables the prompt and accurate identification of clinically significant Acinetobacter species when used with the improved database.